Empathy in Our Moral Assessment of Violence: A Comparative Analysis of the Approaches of Seneca, Sontag and Butler. - Manuela Irarrázabal (Think Pieces, 2014)
To download this article, please click here. Questions concerning the relationship between emotional and moral response, and between emotional reaction and effective political reaction have been a matter of discussion for Seneca, Judith Butler and Susan Sontag. This paper aims to compare their attempts at laying the foundations of our moral assessment of notions of shared human vulnerability as a way of rethinking the cycles of retributive violence. Susan Sontag has focused her attention on how photographs can convey the sufferings of those depicted so that they may influence our evaluation of war and, most importantly, our capacity to react in accordance with that evaluation. Judith Butler, in turn, has drawn our attention to the question of our ethical duties towards those who remain anonymous or who are regarded as distant, and the problem imposed by the controversial reliability of mainstream media on registering and reporting the sufferings of war, imprisonment and immigration. In light of these questions, Seneca’s programmatic attempt at establishing a way of actively responding to others’ sufferings based on the recognition of our own enormous capacity to fail, as opposed to the pity and sorrow that they may (or may not) cause us, is a valuable approach to consider. Awareness of human failure is regarded by Seneca as the foundation for stopping retributive violence and a call for humanitarianism, as it appeals to a common standpoint from which one may understand – and condemn – the other’s point of view. Here I would like to emphasise how certain aspects of Seneca’s attempt at establishing mindfulness of our own capacity to err and to suffer from other’s errors as the starting point for his claim for humanitarian reaction to the moral mistakes of others, bares some resemblance to Butler’s attempt at making the notion of ‘vulnerability’ the basis of claims for non-military political solutions to violence.